The Influence of Discipline, Motivation and Incentives on Employee Performance at the Regional Secretariat of the Regency Ogan Komering Ilir - Pramesti, Farid Intan; Djazuli, Abid; Choiriyah, choiriyah (International Journal of Marketing & Human Resource Research, 2025)
This study aims to investigate the impact of discipline, motivation, and incentives on employee performance at the Regional Secretariat of Ogan Komering Ilir Regency. This type of research is descriptive. The variables used by the researcher are discipline, motivation, incentives, and performance. The sample in this study consisted of 104 employees of the Regional Secretariat of Ogan Komering Ilir Regency selected through Proportionate Stratified Random Sampling. The data used in this study were primary data collected through questionnaires and secondary data from previous research. The data analysis technique used is multiple linear regression and moderated regression analysis, performed with the SPSS Program, Version 26. The results of this study indicate that, collectively, discipline, motivation, and incentives have a significant impact on the performance of employees at the Regional Secretariat of Ogan Komering Ilir Regency. Partially, (1) discipline significantly affects employee performance at the Regional Secretariat of Ogan Komering Ilir Regency, (2) Motivation has an influence does not significantly affect employee performance at the Regional Secretariat of Ogan Komering Ilir Regency, and (3) incentives significantly affect employee performance at the Regional Secretariat of Ogan Komering Ilir Regency